MONITORING THE ABUNDANCE OF MACAWS FOR TEN YEARS IN THE MIDDLE BASIN OF THE SAMIRIA RIVER, LORETO, PERU - ORBE ALVAN, Segundo Artidoro (2020)
The climatic changes that have occurred in the last decades have influenced the trends and population fluctuations of many Amazonian species, including the macaws. Between 2006 and 2015, macaws were quantified on the mid watershed of the Samiria river in Peru. Point counts distributed along 8 aquatic transects on the Tacshacocha and Huishtococha sectors were applied during growing and dry seasons to determine macaw abundance and the possible changes due to climatic events. With a total of 4225 pseudo-replications in 72 counting point stations, there were 65 149 macaw sightings. We recorded five species: Orthopsittaca manilatus, Ara ararauna, Ara severus, Ara chloropterus and Ara macao. The result displayed high consistency during the ten years, with O. manilatus being the most abundant species and the rarest species A. chloropterus and A. macao; with both groups showing differences between the Tacshacocha and Huishtococha. The macaw population fluctuated throughout the years. The species A. ararauna, A. severus and A. macao had a decline in their populations, yetthis trend was not significant and their populations have remained stable during the last decade. Orthopsittaca manilatus and A. chloropterus are the only species whose populations have increased with indications of the dry generated in 2010 due to the seasonality of the Marañon and Amazonas river water levels.